2022
DOI: 10.1039/d2se00182a
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oxygen pressure on the discharge performance of potassium–oxygen batteries

Abstract: Applying high oxygen pressure drastically improves the discharge performance of potassium-oxygen batteries. High oxygen pressure can also prevent parasitic reactions leading towards K2SO4 and K2CO3 induced by oxygen depletion within the cathode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…This indicates strong oxygen transport limitations at the higher rates. 25 In Figs. 3d-3f, the simulated KO 2 volume fraction θ KO ,dep 2 after discharge is displayed.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…This indicates strong oxygen transport limitations at the higher rates. 25 In Figs. 3d-3f, the simulated KO 2 volume fraction θ KO ,dep 2 after discharge is displayed.…”
Section: Resultsmentioning
confidence: 98%
“…From previous reports, it is apparent that oxygen transport is governing the discharge performance. 25 A simulation of the oxygen concentration c O2 along discharge was conducted. The c O2 distributions at different depths of discharge (DoD) for both J = 0.1 mA cm −2 and J = 0.5 mA cm −2 are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen pressure could play a very significant role in performance. 113,114 Higher pressure enables more O 2 to reach the active carbon sites and thus a higher discharge capacity. Hickey et al found that the discharge capacity increased by 10% as the O 2 pressure increased from 1 atm to 10 atm.…”
Section: Crystal Growth Of LImentioning
confidence: 99%